2012
DOI: 10.1159/000331776
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality as a Cardiovascular Risk Marker in the General Population: Results from the Gutenberg Health Study

Abstract: Background: Type D personality is considered as an independent risk factor for morbidity and mortality in cardiovascular patients and a vulnerability factor for distress in the general population. Because representative community studies are rare, we sought to determine the prevalence of type D personality and its relationship with demographic characteristics, different features of mental disorders, cardiovascular risk factors, health behavior, endothelial function and cardiovascular biomarkers in the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 104 publications
7
42
0
6
Order By: Relevance
“…Type D personality was found in around one-sixth of the general population [24, 25], and the prevalence of type D personality in cardiac patients varied widely from 5.3% [26] to 53% [3]. In the present study, a similar prevalence (29.2%) of type D personality was found among patients with haemorrhoids.…”
Section: Discussionsupporting
confidence: 77%
“…Type D personality was found in around one-sixth of the general population [24, 25], and the prevalence of type D personality in cardiac patients varied widely from 5.3% [26] to 53% [3]. In the present study, a similar prevalence (29.2%) of type D personality was found among patients with haemorrhoids.…”
Section: Discussionsupporting
confidence: 77%
“…One study reported a reduction of 54% of endothelial progenitor cells in Type D compared with non-Type D persons (Van Craenenbroeck et al, 2009), however, another study reported no association of Type D with endothelial dysfunction (Beutel et al, 2012). To our knowledge, we are the first to examine the association of Type D with endothelial function in a large population-based study, assessing a wide variety of biomarkers, and showing a significant association.…”
Section: Discussionmentioning
confidence: 86%
“…In the same vein, it is likely that psychotherapy protocols focusing on depressive symptoms in cardiac settings may overlook other important negative affective components associated with depression, such as anxiety, anger, hostility, distress or a general disposition toward negative affectivity and personality traits [43,45,46,47,48,49,50,51,52]. These components that are associated with depression, if untreated, could interfere with medical outcomes due to a combination of the effects on inflammation, catecholamines, heart-rate variability and endothelial function, along with effects on health-promoting behaviors [53].…”
Section: Is Depression the Right Target?mentioning
confidence: 99%